Openbaar en particulier. Amsterdamse weeshuizen en hun typologie (Bulletin KNOB, 2010)
The diversity of religious denominations in the Dutch Republic also had consequences for institutions like orphanages in the seventeenth century. In Amsterdam the various religious denominations also interfered with the care of orphans whose parents had belonged to the religious denomination in question without having been burghers of Amsterdam. Because of the large number of orphanages a comparison of the architecture of these institutions in the seventeenth and eighteenth centuries is interesting. The urban orphanages, closely connected with the town, were by far the largest; in spite of this the Burgerweeshuis (public orphanage) was hardly visible because older, already existing buildings were used.The Diaconie Weeshuis and the Aalmoezeniers Weeshuis, however, were given a large accommodation; from their architecture it is apparent that these were in fact also buildings owned by the town authorities. Both buildings were constructed on interesting locations in the town centre. Except for two entrances and a double amount of space in order to split the orphans into groups of girls and boys, there is hardly any recognizable typology noticeable in the group of orphanages as a whole. The nonurban orphanages were built in considerably less prominent places in town, compared to the urban institutions mentioned. An exception was the so-called Collegianten Weeshuis, which could move into an already existing building on Herengracht, where a second building was soon added in the inner courtyard because of the expansion necessary before long.The most prominent orphanage built in the eighteenth century was the Maagdenhuis, constructed on Spui. Although it was a Roman Catholic institution, this architecture has an urban character. In the seventeenth century it is remarkable to mention that a naval warehouse and two orphanages showed architecture that was closely related to the newly built Town Hall on Dam square. It was not so much the function of the buildings that was the main concern, but rather the element of urban authority and power.